Maternal health literacy and anxiety among pregnant women receiving antenatal care: A cross-sectional study - Anggie Pradana Putri; Ady Irawan.AM; Lilik Hanifah (Indonesian Nursing Journal, 2026)
Background: Anxiety during pregnancy can affect maternal well-being and engagement with antenatal care. Maternal health literacy may help women understand pregnancy-related changes, evaluate health information, and make appropriate decisions, but its association with anxiety remains underexplored in Indonesian antenatal care settings. Purpose: This study examined the association between maternal health literacy and anxiety among pregnant women receiving routine antenatal care. Method: A cross-sectional correlational study was conducted among 140 pregnant women attending primary maternal healthcare facilities in Central Java, Indonesia. Participants were recruited using consecutive sampling. Maternal health literacy was measured using the Indonesian version of the 48-item Maternal Health Literacy Inventory in Pregnancy, while anxiety was assessed using the Indonesian version of the Generalized Anxiety Disorder-7 scale. Descriptive statistics summarized participant characteristics and study variables. The association between maternal health literacy and anxiety was analyzed using Spearman’s rank correlation test. Result: The mean maternal health literacy score was 177.3 ± 21.4, and the mean anxiety score was 6.8 ± 4.5. Most participants reported minimal or mild anxiety, while 23.6% experienced moderate-to-severe anxiety. Maternal health literacy was negatively correlated with anxiety scores (Spearman’s rho = -0.412; p < 0.001). Conclusion: Higher maternal health literacy was associated with lower anxiety among pregnant women. Antenatal care should help women not only receive pregnancy information but also interpret and use it confidently. Longitudinal and intervention studies are needed to test whether nurse-led literacy and digital education programs can reduce anxiety during pregnancy